On a New Application of Almost Increasing Sequence to Laguerre Series Associated with Strong Summability of Ultrapherical Series - Sahani, Suresh Kumar; Pokharel, Jagat Krishna; Paudel, Gyan Prasad; Tiwari, S.K. (Nepal Journal of Mathematical Sciences, 2023)
The concept of summability of infinite series has been utilized in virtually every field of scientific application, including the enhancement of signals in filters, the acceleration of the rate of convergence, orthogonal series, and approximation theory, to name just a few. In addition, by making use of the main theorem, a collection of new well-known arbitrary findings have been obtained. Taking into account the appropriate conditions of a prior result, which result was produced, verifies the conclusions of the current study.